ANALYSIS OF INDIGENOUS MATERIALS USED IN INDIAN PAINTED AND PRINTED TEXTILES - Joshi, Nitika; Bhagat, Simmi (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The term "indigenous" can refer to several diverse materials, including those that are easily obtainable in the vicinity, such as dyes obtained from different parts of plants, as well as various minerals. Traces of similar materials have also been discovered during excavations at several sites across the country. Due to the harsh environmental conditions in different regions, evidence of Indian textiles has been found in multiple literary works and at historical sites. These fabrics are being kept in museums all around the country for posterity's sake. India's painted and printed textiles are an essential part of the nation's heritage. Because these textiles are endangered due to their organic nature, museums work to conserve and preserve them. Several museums, including the National Museum in Delhi and the Calico Museum in Ahmedabad, among others, display these beautiful textiles. This paper analyses the different sustainable raw materials that have been used for centuries in India's painted and printed textiles. This article reviews India's painted and printed textiles, their sources of materials, and their properties. Mainly, secondary resources have been used for data collection. Many heritage textiles, because of the prevailing use of synthetic dyes, are losing their authenticity. Moreover, this paper will help Conservators, curators, and researchers working in textile conservation and art & culture to use this information to help preserve these textiles.